Sharing experiences and networking by Putri Saniah Megat Abd Rahman (President 2005/2007 & 2007/2008) - Megat Abd Rahman, Putri Saniah (2015)
PPM is a good platform for knowledge sharing, networking and professional development at national and international level. PPM's affiliation with other associations, organisations and institutions facilitate PPM to develop and organise traning programs, conferences and quality management services and activities. The programs initiated benefit all librarians from all types of libries in Malaysia.